ARDS : acute respiratory distress in adults - Evans, Timothy W; Haslett, C; Petty, Thomas L (Chapman & Hall, 1996)
National Heart & Lung Institute, London, U.K. Text on the basic mechanisms, physiology, clinical assessment, and therapeutic interventions for ARDS, for practitioners and students. 51 contributors, 20 U.S.
Keywords: Respiratory Tract Diseases; pneumologie a ftizeologie; nemoci dýchací soustavy